Implementación de un software de educación especial que motive y facilite el desarrollo del lenguaje en los niños con síndrome de down utilizando la metodología (dsdm), en el centro de rehabilitación San Miguel De Salcedo en el periodo junio 2013 - agosto 2014 - Hinojosa Pacheco, Manuel Rodrigo (2014)
San Miguel FUNESAMI Special Kids Foundation, is located in Salcedo town from Cotopaxi province, which did not have a software for special education, for language teaching. It has seen on the necessity to contribute to the implementation software for special education that motivates and facilitates development of language in children with Down syndrome. The present research consists of three chapters, the first chapter reflects the theoretical foundations that helped us to collect bibliographic information necessary for the development of research and it raided methods and tools to be used as the interview, survey and observation moreover technology tools that will help in Software in development. In the second chapter is all about the interpretation of results, it is the data obtained from surveys and interviews Carrie bout to the beneficing population of the research, in which reflex necessary to implement a software of special education, which will help as a complement to the traditional teaching method, using technology as a means to assist in the process of language development in children with Down syndrome. In the third chapter shows the proposal to be developed. Which will be the construction and application of the software for special education that motives and facilitates the teaching of language.